DIVIDEND POLICY MODERATES GROWTH OPPORTUNITY, FREE CASH FLOW, AND DEBT POLICY ON THE FIRM VALUE - Fera Tjahjani; Stefen Satria Tanoto; Nawang Kalbuana (CV. Adiba Aisha Amira, 2025)
Purpose: This research is conducted to know the role of dividend policy as a moderating variable on the effects of growth opportunity, free cash flow, and debt policy on the firm value. Methods: Purposive sampling method was used to obtain 23 primary consumer goods companies from Indonesia Stock Exchange (IDX) for year 2018 – 2020. Analysis data: multiple regression analysis technique was used to test hypothesis. Result and discussions: growth opportunity has no effect on the firm value. Otherwise, free cash flow influence firm value positively and debt policy has negative effect on the firm value. Dividend policy cannot moderate the relationship of growth opportunity, free cash flow, and debt policy to the firm value.